2018
DOI: 10.37358/rc.18.3.6153
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Progesterone on Immunohystochemical Markers in Endometriosis

Abstract: Endometriosis, one of the most common gynecologic pathologies, is defined as an inflammatory, estrogen-dependent disease characterized by the growth of endometrial stroma and glands outside the uterine cavity. It is a multifactorial disease, conditioned by genetic and immune factors and triggered by hormonal and environmental factors. Estrogen receptors (ER) and progesterone receptors (PR) expression is significantly modified in endometriotic tissue, compared to normal endometrium. We performed a prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…In our study, the highest percentage of positive urine culture was observed for Escherichia Coliestimated 27% as we can see in the Table 2 and figure 3. Table 3 INTRA-AND POSTOPERATIVE CHARACTERISTICS Data existing in specialized literature agree that female gender, having positive urine culture with mostly Proteus species is associated with a struvite composition of the calculi [2,22]. According to our data, the positive urine cultures were mostly revealed in the struvite group and E.Coli was the most frequent isolated bacteria (16 cases -42,11% in this group).…”
Section: Resultssupporting
confidence: 72%
“…In our study, the highest percentage of positive urine culture was observed for Escherichia Coliestimated 27% as we can see in the Table 2 and figure 3. Table 3 INTRA-AND POSTOPERATIVE CHARACTERISTICS Data existing in specialized literature agree that female gender, having positive urine culture with mostly Proteus species is associated with a struvite composition of the calculi [2,22]. According to our data, the positive urine cultures were mostly revealed in the struvite group and E.Coli was the most frequent isolated bacteria (16 cases -42,11% in this group).…”
Section: Resultssupporting
confidence: 72%
“…In these patients, the therapy used was ureteroscopy and laser lithotripsy. Using laser lithotripsies, trauma of the urothelium [31][32][33][34][35] is usually lower compared to other types of lithotripsies [36] but considering the fragmentation rate of 90-96% and lower costs compared to laser fibers [37], we used the ballistic lithotomy with the 2.4 F probe that was inserted through the semi-rigid ureteroscope with a stone free rate of 98% of cases after fitting a 4.8-6-6 Ch ureteral stent with a 24-25 cm length of polyurethane aliphatic material. The choice of the type of stent was made on the basis of the results of the prospective study of Scarneciu et al which demonstrates that choosing the type of stent depending on the composition does not bring benefits in terms of the patient's quality of life during stenting [38].…”
Section: Resultsmentioning
confidence: 99%
“…Local invasion and metastasis of malignant tumors are complex processes that start with the disruption of normal cell-cell adhesion and detachment of malignant cells from the primary tumor; immunohistochemical analysis is essential, regardless of the type of cancer being investigated [2][3][4][5]. Tumor progression and metastasis are based on several successive stages including: separation of tumor cells from the primary tumor, attachment to the basal vascular membrane followed by its destruction and entering the blood and/or lymphatic circulation, leaving blood vessels and resettling in target organs as metastasis [6,7].…”
mentioning
confidence: 99%